THE SCIENTIFIC HERITAGE OF THE TIRMIDHIS: THE IMPORTANCE OF JUSTICE IN STRENGTHENING YOUTH IDEOLOGY (American Journal of Pedagogical and Educational Research, 2026)
This article thoroughly examines the essence and meaning of the concept of justice in the scholarly and spiritual heritage of great thinkers who emerged from the land of Termez – particularly Imam Tirmidhi and Hakim Tirmidhi. The study analyzes, based on the Holy Qur’an, the role of justice within the Islamic ethical system, as well as its significance in human development, spiritual education, and societal stability. Furthermore, it provides a scholarly justification of how justice manifests not only as a socio-legal principle but also as an inner spiritual and moral virtue, and highlights the priority aspects of cultivating it in the upbringing of youth.